Apocalypto [videorecording (DVD)] - Gibson, Mel; Gibson, Mel; Youngblood, Rudy, 1982-; Hernandez, Dalia; Brewer, Jonathan (Touchstone Home Entertainment : Distributed by Buena Vista Home Entertainment, 2007)
As the Mayan kingdom faces its decline, the rulers insist the key to prosperity is to build more temples and offer human sacrifices. Jaguar Paw is a young man who is captured for sacrifice, but flees to avoid his fate. He is taken on a perilous journey to a world that is ruled by fear and oppression, where a harrowing end awaits him. Through a twist of fate and spurred by the power of his love for his woman and his family he will make a desperate break to return home and to ultimately save his way of life.